(untitled) (Shahid Kirti Multidisciplinary Journal, 2026)
The study has analyzed the fertility variation of Danuwar females between the ages of 15-49 years in Lalitpur District, Nepal as the number of living children as the major source of fertility measurement. Although Nepal is facing a decline in its national fertility rates, the marginalized ethnic groups and consequently they are under-represented in the empirical studies and thus may obscure recurrent disparities in reproductive performance. This was done by a cross-sectional survey (289 women) on a community level and by using descriptive statistics and chi-square analysis, the extent to which the socio-demographic, behavioral, and attitudinal correlates of fertility were evaluated. The age was significantly related to the number of living children (χ 2 = 21.968, p < 0.001), which showed that there was a positive relationship between the advancing age and cumulative fertility. Experience with contraceptives and intentions to have children were also important: women who had ever used family planning methods and those who desired to have two or more children were more likely to have two or more children also implying that limitation rather than spacing drives contraceptive practice. Conversely, education, employment, household income, communicative relationship with a spouse, and the knowledge concerning modern contraception did not significantly relate to the fertility results. These results show that reproductive life-course factors are stronger in determining fertility in this marginalized group than socio-economic and attitudinal ones. The study highlights the importance of earlier adoption of contraceptives, enhanced reproductive counseling, and measures that deal with ingrained socio-cultural values, as per priorities of reproductive health in Nepal and the obligation to gender-equality